Nexus between remittance and poverty in Nepal - Tiwari, Sagar (Shaheed Smriti Journal, 2022)
This study is the analysis to examine the nexus between poverty and remittance in Nepal. The study found that near about one quarter people are living below the poverty line out of which One third percent people are poor who don’t receive remittance where one fifth percent people are poor who received remittance. Remittance has less effect in the poverty of Terai region. There is drastic difference between the per capita remittance received by an individual in the poorest and the richest consumption quintile. The households have one more additional year of education, experienced two percent less probability of being poor. Migration of an additional member caused to reduce 2.6 percent poverty on the household level. The research design for this study is both qualitative and qualitative with using cross sectional secondary data of NLSS III. By using the STATA software, the study has used the Probit Model as remittance and poverty effect unction to observe probability of being non poor.